Realcalinização eletroquímica de estruturas de concreto armado carbonatadas inseridas no meio urbano:influência de características da estrutura no comportamento do tratamento - Ribeiro, Philippe Hypólito Lins Cabral (2009)
A serious problem that can damage reinforced concrete structures in urban environments is the corrosion of steel reinforcement, which takes place mainly due to chloride marine regions penetration into concrete and its carbonation. For this last case, the electrochemical realkalisation (ERA) technique has been recently developed as a rehabilitation method aimed on re-establishing concrete alkalinity, which leads to the re-establishment of the steel passivity. This way, this research aimed to study the influence of concrete characteristic and thickness of concrete cover on the ERA. For this purpose, prismatic concrete specimens were cast with two different thickness of reinforcement concrete cover, two types of Portland cements (Brazilian cements type IV and V) and water to cement ratios of 0,55 e 0,65. The specimens were previously carbonated in a chamber with saturated atmosphere (100% of CO2). After loosing the passivity, the specimens were subjected to ERA treatment and the process was monitored by spraying thymolphthalein indicator and electrochemical measurements of half-cell corrosion potencial (Ecorr), corrosion rate (icorr) and superficial resistivity (ρ). These electrochemical measurements were also done along the carbonation period. For the ERA treatment, a sodium carbonate solution (1M) was used as electrolyte, a titanium mesh as the anode and a current density of 2 A/m²concrete. Measurements of alkalinity were carried out for reference (REF), carbonated (CARB) and realkalysed (ERA) concretes. The results pointed out that the treated specimens presented higher relative alkalinity than the carbonated specimens and this confirms the efficiency of the ERA, concerning the reestablishment of the concrete cover alkalinity. The alkalinity provided by the treatment is a function of total electric charged passed, which weakens as total charge passed increases. Pozolanic concretes needed higher electric charged passed than OPC concretes to complete realkalisation of concrete cover, although the last one reached higher relative alkalinity levels. This indicates that the effectiveness of concrete realkalisation with pozolanic addition seems to be more difficult. In addition, after the ERA treatment, pozolanic concretes tend to present longer depolarization periods to repassivate reinforcements. The specimens with thicker concrete cover required higher electric charged passed and more time to complete the treatment and, afterwards, tend to present a shorter time to repassivate reinforcements. It was observed that Ecorr values indicate a reinforcement repassivation tendency. On the other hand, although there is a decrease tendency of icorr values, more time is needed to give definitive responses about reinforcement repassivation. Finally, the electric charged passed, only enough to complete realkalisation of whole concrete cover, has fundamental influence on the efficiency of the treatment and the depolarization period until repassivation. On the other hand, electric charged passed, exceeding that enough to complete realkalisation of whole concrete cover, doesn t present influence on repassivation of steel reinforced.